(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Agriculture is critical to the growth of agrarian countries like India. Agriculture-related issues have long been a roadblock to the country’s growth. Smart agriculture, which involves updating existing agricultural techniques, is the only answer to this issue. As a result, the suggested approach seeks to use automation and IoT technology to make agriculture smart. Crop growth monitoring and selection, irrigation decision assistance, and other applications are enabled by the Internet of Things (IoT). To modernize and increase agricultural production, a Microcontroller Pi-based IoT watering solution is recommended. The major purpose of this research is to grow crops with the least amount of water possible. Most farmers spend hours throughout the fields in order to focus on groundwater resources to plants at the proper time. Groundwater contamination should be enhanced, and the complexity of the system circuit should be reduced. The protocol determines the quantity of water necessary analysis of the results obtained from the sensors. Six sensors detect the temperature of the food of the soil, but also the precipitation, temperatures, and duration of daylight each day, and send the data to the mobile node. Dependent on these characteristics, the proposed systems must calculate the quantity of water needed for irrigation. The usage of Crop Monitoring (PA) with virtualization is the system’s key advantage, as it will evaluate and use of water nitrates while boosting crop yields and aid in analyzing field condition.